A pilot replication study of two PER3 single nucleotide polymorphisms as potential genetic markers for morning and evening earliness-lateness. Issue 4 (4th July 2017) - Dorokhov, Vladimir B.; Puchkova, Alexandra N; Taranov, Anton O.; Slominsky, Petr A.; Vavilin, Valentin A.; Ivanov, Igor D.; Popov, Alexey V.; Nechunaev, Victor V.; Aǐzman, Roman I.; Budkevich, Elena V.; Budkevich, Roman O.; Donskaya, Olga G.; et al.
Abstract: Polymorphisms in genes of circadian system family seem to be of most importance for understanding of mechanisms underlying self-assessed individual variation in morning–evening preference. A review of earlier reported positive findings indicated that, at least, four polymorphisms in period circadian clock 3 (PER3) showed significant association with, at least, one of sub-constructs of a morningness–eveningness scale. However, similar to other candidate gene studies, these studies suffer from increased likelihood of false positive findings. We tried to replicate some of the most recently published positive results on associations of sub-traits of morningness–eveningness with two PER3 non-synonymous single nucleotide polymorphisms. DNA from buccal swabs was collected from healthy residents of three Russian cities, Moscow ( N  = 149) and Novosibirsk and Stavropol ( N  = 248). The tested hypotheses were formulated in accord with the earlier reported positive findings: the rare alleles might be linked to a higher score on (i) morning earliness–lateness scale (rs2640909, Moscow data-set) and (ii) both morning and evening earliness–lateness scales (rs228729, Novosibirsk and Stavropol datasets). The results provided support for the former hypothesis. These and earlier reported results highlighted several critical issues that remained to be addressed in future independent replications of positive findings on potential genetic markers for morning and evening earliness–lateness.